The Political Economy of Climate Change Adaptation - Sovacool, Benjamin K. author. aut Link
XI, 226 p.
Keywords: Drawing on concepts in political economy, political ecology, justice theory, and critical development studies, the authors offer the first comprehensive, systematic exploration of the ways in which adaptation projects can produce unintended, undesirable results. This work is on the Global Policy: Next Generation list of six key books for understanding the politics of global climate change.